Factors associated with lack of viral suppression in human immunodeficiency virus-infected male patients treated with anti-retroviral therapy at Bach Mai hospital, Hanoi - Thi Duc, Hanh Tran; Thi Dinh, Thanh; Duy Do, Cuong; Nguyen, Ha Thi; Vu Phuong Dang, Linh (International Journal Of Community Medicine And Public Health, 2025)
Background: Viral suppression following anti-retroviral therapy (ART) is one of the most effective factors determining human immunodeficiency virus (HIV) treatment success. However, certain numbers of HIV-infected patients do not experience viral suppression despite ART initiation, which ultimately might lead to treatment failure. Method: A cross-sectional study was conducted including 194 male patients enrolled at the out-patient clinic, the Centre for Tropical Diseases, Bach Mai hospital, Vietnam. Data was analyzed using Stata 12.0.20 for Man-Whitney, Chi-square test/ Fisher’s exact test, and multivariable logistic regression with statistically significant p<0.05. Results: The results show that being men who have sex with men (aOR=12.14, 95% CI: 1.48-99.49), having low CD4 T cell counts (aOR=269.58, 95% CI: 4.94-14721.27), living in rural areas (aOR=4.63, 95% CI: 1.04-20.57), and not having preventive tuberculosis treatment (aOR=9.92, 95% CI: 1.17-84.10), have increased odds of having detectable viral loads (VL). On the contrary, opportunistic infection was negatively associated with a lack of viral suppression (aOR=0.21, 95% CI: 0.05-0.96). Conclusions: The results suggest that intervention programs should focus on patients living in rural areas, having low CD4 T cell counts, acquiring opportunistic infection, and MSM patients.